STUDY OF IMPACT OF INDIAN TRADITIONS & CULTURAL PRACTICES FOR PROMOTING SUSTAINABLE FASHION INDUSTRY - Thakur, Manasi Nachiket; Atre, Avadhut (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian traditional textiles, garments and clothing has a huge impact on the fashion industry today. Focus on Sustainability has created lot of opportunities for the stakeholders to work. As part of this research we touch on the following aspects of the fashion industry - Sustainable Environment, Livelihood, Businesses, Practices & education. This paper studies the various traditional and cultural practices in the Indian society which impacts the way fabrics and garments are used. It also documents and analyses apparel brands which believes in sustainability practices to run their unique business. To generate sustainable livelihood, the youth of the country should undergo vocational training suitable to fashion industry in their native language. The paper studies various opportunities in education related to the Fashion ecosystem available in India. Thestudy will document the philosophy, skills, opportunities and collective commitment for promoting sustainable fashion industry.